2015
DOI: 10.1002/eat.22447
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic examination of the temporal patterns of affect and eating disorder behaviors in anorexia nervosa

Abstract: Objective Evidence supports the presence of significant variability in the timing of affective experiences and eating disorder (ED) behaviors across ED populations. This study examined the naturalistic timing of affective states and ED behaviors in anorexia nervosa (AN). Methods Women (N = 118) with full or subthreshold DSM-IV AN completed two weeks of ecological momentary assessment (EMA) involving self-reports of affect and ED behaviors. Patterns of positive affect, negative affect, and tension/anxiety acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
(25 reference statements)
4
16
0
Order By: Relevance
“…Meal skipping is common in ED patients and has previously been reported on [24,25]. In this study, number of daily or weekly meals did not differ significantly between ED-good condition and controls.…”
Section: Discussionsupporting
confidence: 57%
“…Meal skipping is common in ED patients and has previously been reported on [24,25]. In this study, number of daily or weekly meals did not differ significantly between ED-good condition and controls.…”
Section: Discussionsupporting
confidence: 57%
“…It should be noted that the datasets used for study 1‐AN and study 2‐BN have been utilized in several other studies. For example, the AN dataset has been used in a variety of papers examining specific aspects of the emotion‐behavior relationship in AN (Engel et al, ; Haynos, Berg, & Cao, ; Lavender, Utzinger, and Crosby, ). Similarly, the BN data set has been utilized in several studies, which again have examined emotion‐behavior patterns (e.g., Berg et al, ; Crosby et al, ; Smyth et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Most notably, the sample size is small compared to other EMA studies on eating disorders (Engel et al, 2016, 2013; Lavender et al, 2016). However, sufficient measurements were recorded to carry out LMM analysis, but the results need to be considered as exploratory.…”
Section: Discussionmentioning
confidence: 93%
“…Variations in time of tension and anxiety, which are suspected to correlate with emotion identification on a trait level (Eizaguirre et al, 2004; Gilboa-Schechtman et al, 2006), have been observed in individuals with AN (Lavender et al, 2016). A study on emotion identification in borderline personality disorder (BPD) identified a strong association of current levels of aversive tension and the ability to label specific emotions (Wolff et al, 2007).…”
Section: Introductionmentioning
confidence: 99%